2023
DOI: 10.48036/apims.v18i4.668
|View full text |Cite
|
Sign up to set email alerts
|

Safety of Remdesivir in Covid Patients with Acute or Chronic Kidney Disease

Abstract: Objective: The aim was to assess the safety of Remdesivir in Patients with Acute and Chronic Kidney DiseaseMethodology: Quasi-experimental study was conducted at the Pak Emirates Military Hospital Rawalpindi from March 2021 to April 2022. A sample was collected through a non-random sampling method, recruiting those who were diagnosed with pneumonia caused by the COVID-19 virus. A total of 56 patients with acute or chronic kidney disease were the participants of our study. The inclusion criterion was patient wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…In another case study, an obese patient developed abrupt hepatic failure after receiving remdesivir therapy (28). Some studies, on the other hand, found no significant differences in liver and renal function tests from the baseline (29,30).…”
Section: Discussionmentioning
confidence: 97%
“…In another case study, an obese patient developed abrupt hepatic failure after receiving remdesivir therapy (28). Some studies, on the other hand, found no significant differences in liver and renal function tests from the baseline (29,30).…”
Section: Discussionmentioning
confidence: 97%